G1/S Cell Cycle Blockers and Inhibitors of Cyclin-Dependent Kinases Suppress Camptothecin-Induced Neuronal Apoptosis - Park, David S. (J Neurosci, 1997)
Previous studies have demonstrated that G1/S cell cycle blockers and inhibitors of cyclin-dependent kinases (CDKs) prevent the death of nerve growth factor (NGF)-deprived PC12 cells and sympathetic neurons, suggesting that proteins normally involved in the cell cycle may also serve to regulate neuronal apoptosis. Past findings additionally demonstrate that DNA-damaging agents, such as the DNA topoisomerase (topo-I) inhibitor camptothecin, also induce neuronal apoptosis. In the present study, we show that camptothecin-induced apoptosis of PC12 cells, sympathetic neurons, and cerebral cortical neurons is suppressed by the G1/S blockers deferoxamine and mimosine, as well as by the CDK-inhibitors flavopiridol and olomoucine. In each case, the IC(50) values were similar to those reported for inhibition of death induced by NGF-deprivation. In contrast, other agents that arrest DNA synthesis, such as aphidicolin andN-acetylcysteine, failed to block death. This suggests that the inhibition of DNA synthesis per se is insufficient to provide protection from camptothecin. We find additionally that the cysteine aspartase family protease inhibitor zVAD-fmk inhibits apoptosis evoked by NGF-deprivation but not camptothecin treatment. Thus, despite their shared sensitivity to G1/S blockers and CDK inhibitors, the apoptotic pathways triggered by these two causes of death diverge at the level of the cysteine aspartase. In summary, neuronal apoptosis induced by the DNA-damaging agent camptothecin appears to involve signaling pathways that normally control the cell cycle. The consequent death signals of such deregulation, however, are different from those that result from trophic factor deprivation.